Pelatihan UnoArduSim dan Aplikasi Arduino untuk Pelajar SMKN 2 Samarinda - Sunu Pradana; Khairuddin Karim; Onglan Nainggolan (Universitas Negeri Makassar, 2018)
This paper describes the results of UnoArduSim training activities and Arduino applications for studentsof Samarinda Vocational High School 2. This activity is an answer to several problems and challenges in the worldof education, especially in SMK 2. The problems include the development of the latest technological devices thatare very fast, the synergy between vocational education providers that need to be improved, the relevance ofgraduates to industrial needs, and continued interest in learning. This activity was carried out for two days anddivided into several stages of activities, namely the delivery of theories about the Arduino system and subsequentlygiven a tutorial on using the UnoArduSim along with the practice of setting up Triac with Arduino and usingpotential ometers as input to the Arduino system. The activity ended with training on the use of Arduino Uno withLCD shield which is used both as input and output. The trainees were attended by 15 students from the ElectricalEngineering Department who were divided into 4 groups according to the number of practicum modules. Thevalidation of the results of the training was carried out by filling out questionnaires by participants. Thequestionnaires consisted of two parts, namely quiz and questions. The quiz aimed at measuring the level ofabsorption of information by trainees' students whereas questions (without scores/answers) answered by participantsto get feedback on the implementation of PKM activities. The assessment was done automatically by Google Form.The results obtained were: for the coverage of material as much as 86.7% stated ―Yes‖. The question about the levelof training needs for the younger students: 93.3% participants stated that the younger students need this kind oftraining.